Isolation and characterization of cellulose synthase gene from Roselle (Hibiscus sabdariffa L.) - Seyedi, Seyedehsareh (2014)
Hibiscus sabdariffa (Roselle) has the potential to be an alternative fibre source for cellulose as a strengthening material in polymer composites. A literature survey has shown scant information regarding utilization of this fiber as reinforcing material. Although roselle was hypothesized to be a potential natural fibre source, there is no study focusing on the fundamental genetics underlying the cellulose biosynthesis machinery in roselle. Isolation of CesA gene is important to understand the biosynthesis pathway in roselle. Therefore, the first cellulose synthase gene (HsCesA1) of H. sabdariffa was isolated and characterized. Full-length HsCesA1 cDNA of 3528 bp was isolated using RACE PCR, and the start and stop codons, poly A signal, poly A tail, 3´ UTR and 5´ UTR were identified using in silico analyses. The full-length HsCesA1 gene with a total length of 5489 bp, which consisted of 12 exons, 11-introns and a promoter region of 737 bp was also isolated using PCR walkin and genome walking repectively. Several important and conserved characteristics were predicted in the HsCesA1 deduced amino acid sequence such as Cellulose-synt, Glycosyltransferase family A (GT-A), bcsA, Zn-finger domain, RING/U-box and domains A and B. These predicted characteristics provided evidence that the isolated gene is possibly a CesA and it belongs to the processive class in the glycosyltransferase family A. Semi-quantitative RT-PCR expression study was carried out on both leaf and stem tissues, it was found that HsCesA1 was expressed in both tissue types and it had similar levels of expression in both young tissues. Phylogenetic and Blast analyses also supported that HsCesA1 might play roles in both primary and secondary cell wall depositions. However, further investigations must be carried out to confirm the function of this HsCesA1. We have isolated the first cellulose synthase gene, full-length HsCesA1 cDNA with total length of 3528 bp (accession no: KJ608192) and full length HsCesA1 gene with total length of 5489 bp (accession no: KJ661223). This study generated some genetic information about the structure and putative function of the cellulose synthase gene in the genome of H. sabdariffa. In the other words, this study provides information on the primary structure of the HsCesA1 gene, which is fundamental for working towards understanding the function of the gene in the roselle plant in the future.